Migration, citizenship and the challenge for security : an ethnographic approach - Innes, Alexandria J. (Palgrave Macmillan, 2020)
This study focuses on the field of security studies through the prism of migration. Using ethnographic methods to illustrate an experiential theory of security taken from the perspective of migrants and asylum seekers in Europe, it effectively offers a means of moving beyond state-based and state-centric theories in International Relations.